Interfacially Polymerized Particles with Heterostructured Nanopores for Glycopeptide Separation. Issue 39 (13th August 2018) - Song, Yongyang; Li, Xiuling; Fan, Jun‐Bing; Kang, Hongjian; Zhang, Xiaofei; Chen, Cheng; Liang, Xinmiao; Wang, Shutao
Abstract: Porous polymer materials are extensively used for biomolecule separation. However, conventional homogeneous porous polymer materials cannot efficiently separate specific low‐abundance biomolecules from complex samples. Here, particles fabricated by emulsion interfacial polymerization featuring heterostructured nanopores with tunable size are reported, which can be used to realize low‐abundance glycopeptide (GP) separation from complex biofluids. The heterostructured surface inside the nanopores allows solvent‐dependent local adsorption of biomolecules onto hydrophilic or hydrophobic regions. Low‐abundance hydrophilic GPs in complex biofluids can be efficiently separated via the hydrophilic region of nanopores in low‐polarity solvent after the hydrophobic region removes high‐abundance hydrophobic proteins and non‐glycopeptides in high‐polarity solvent. It is expected that these particles with heterostructured nanopores can be used for separation of nucleic acids, saccharides, and proteins, and downstream clinical diagnosis. Abstract : Interfacially polymerized particles feature heterostructured nanopores and can achieve low‐abundance glycopeptide (GP) separation from complex biofluids. The heterostructured surface inside the nanopores allows local solvent‐dependent biomolecule adsorption onto hydrophilic or hydrophobic regions. Low‐abundance GPs in complex biofluids are efficiently separated via the hydrophilic region of the nanopores in low‐polarity solvent after the hydrophobic region removes high‐abundance biomolecules in high‐polarity solvent.